2014
DOI: 10.1016/j.jcin.2014.05.011
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of Atherothrombosis and Vascular Response to Primary Percutaneous Coronary Intervention in Women Versus Men With Acute Myocardial Infarction

Abstract: In patients presenting with STEMI undergoing primary PCI, no differences in culprit plaque morphology and factors associated with coronary thrombosis were observed between age-matched men and women. Women also showed similar vascular healing response to everolimus-eluting stents as men did. (Optical Coherence Tomography Assessment of Gender Diversity In Primary Angioplasty: The OCTAVIA Trial [OCTAVIA]; NCT01377207).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
61
0
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 90 publications
(71 citation statements)
references
References 26 publications
5
61
0
3
Order By: Relevance
“…The protocol design, the full methodology and results of the OCTAVIA study have been reported elsewhere. 7 Briefly, OCTAVIA was a prospective, multicenter, investigator-driven study assessing atherothrombotic mechanisms and vascular response to stenting in age-matched women and men presenting with STEMI and undergoing p-PCI with EES (Xience Prime, Abbott Vascular, botic components and thrombus characteristics were classified according to accepted OCT definitions and criteria. 9,10 An "unclassified etiology" was assigned when the core laboratory was unable to adjudicate the occurrence of plaque rupture or erosion because of excessive residual thrombus that obscured the underlying structures.…”
Section: Study Populationmentioning
confidence: 99%
See 2 more Smart Citations
“…The protocol design, the full methodology and results of the OCTAVIA study have been reported elsewhere. 7 Briefly, OCTAVIA was a prospective, multicenter, investigator-driven study assessing atherothrombotic mechanisms and vascular response to stenting in age-matched women and men presenting with STEMI and undergoing p-PCI with EES (Xience Prime, Abbott Vascular, botic components and thrombus characteristics were classified according to accepted OCT definitions and criteria. 9,10 An "unclassified etiology" was assigned when the core laboratory was unable to adjudicate the occurrence of plaque rupture or erosion because of excessive residual thrombus that obscured the underlying structures.…”
Section: Study Populationmentioning
confidence: 99%
“…Qualitative assessment was performed every 0.2 mm, whereas quantitative and morphometric analyses were performed every 0.6 mm along the entire target segment. 7 To determine the effect of plaque characteristics and atherothrombotic components on ISA, multiple OCT pullbacks were integrated. Each cross-section of the stented segment was matched with the corresponding cross-section obtained at baseline and at follow-up, as accurately as possible, based on distances from fiduciary axial landmarks (ie, side branches, calcification, stent edges) ( Figure S1).…”
Section: Oct Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…The observational studies that examined coronary plaque morphology differences in men and women have been far from conclusive, some suggesting lower prevalence of plaque ruptures and thin-cap fibroatheroma (TCFA), higher prevalence of plaque erosions in women and others showing no significant differences. 4,[7][8][9][10] Interestingly, the sex differences in plaque size and morphology were more pronounced in younger patients and attenuated in patients >65 years of age.…”
mentioning
confidence: 98%
“…The observational studies that examined coronary plaque morphology differences in men and women have been far from conclusive, some suggesting lower prevalence of plaque ruptures and thin-cap fibroatheroma (TCFA), higher prevalence of plaque erosions in women and others showing no significant differences. 4,[7][8][9][10] Interestingly, the sex differences in plaque size and morphology were more pronounced in younger patients and attenuated in patients >65 years of age.2,10 In addition to coronary plaque morphology, there were also differences in coronary flow characteristics, with women having higher fractional flow reserve values for any given stenosis and higher degree of mismatch between fractional flow reserve measurements and luminal size.1 Studies demonstrated higher prevalence of coronary microvascular dysfunction with coronary flow reserve <2.5, especially in perimenopausal women.1 In patients with early atherosclerosis without obstructive CAD, men had more structural and functional abnormalities in epicardial coronary arteries, whereas women had greater microvascular dysfunction independent of epicardial endothelial function.11 In contrast, a more recent study using quantitative flow measured by positron emission tomography in a large population with no evidence of ischemia failed to show differences in coronary flow reserve between men and women.12 Finally, nonatherosclerotic causes of symptoms such as coronary vasospasm, coronary dissection, and stress-induced cardiomyopathy were more often observed in women.1 In summary, although there has been increasing understanding of differences and similarities in CAD characteristics between men and women, more information is needed to tailor therapies and improve outcomes in women.In this issue of Circulation: Cardiovascular Imaging, Kataoka et al 13 report the analysis of sex differences in nonculprit coronary plaques as determined by frequency-domain optical coherence tomography (OCT) in a large population of patients who underwent clinically indicated cardiac catheterization and OCT. The authors included both patients with stable CAD and ACS.…”
mentioning
confidence: 99%